Mitigation of Shape Evolution and Supercapacitive Performance of CuCo2S4 Electrodes Prepared via a Simple Solvent Variation Approach - Sagar M. Mane; Komal S. Wagh; Aviraj M. Teli; Sonali A. Beknalkar; Jae Cheol Shin; Jaewoong Lee (Applied Sciences, 2023)
This work demonstrates the evolution of different architectures of Cu-Co bimetallic sulfide on Ni-foam. A simple solvent-changing strategy has been adopted to develop these architectures through a solvothermal approach. When water and ethylene glycol was used as a solvent, the surface of Ni-foam seemed to be covered with a snowflake-like architecture. On the addition of glycerol instead of ethylene glycol, the growth of spongy rectangular prisms from mud-like bricks was initiated. Analyzing electrochemically, both electrodes deliver excellent capacitance. The electrode developed with water and glycerol was found to be richer in terms of capacitive performance, which gives 1459.7 F/gm (5692.8 mF/cm2) at a higher current density of 5 mA/cm2. An over-33% increment in capacitance was noted when compared with the specific capacitance (areal capacitance) of another electrode which can provide 986.6 F/gm (3157 mF/cm2) at the same current density. Both electrodes are richer in terms of providing higher rate capability above 75%, even if the current density is increased by three times. Furthermore, both electrodes deliver long-lasting storage capability, with above 80% capacitance retention over 10,000 charge–discharge cycles even at a higher current density of 60 mA/cm2. This simple solvent-changing approach can be useful for developing electrode materials with outstanding capacitive performance.